Strategi Ketahanan Sosial-Ekonomi Penghayat Kepercayaan Terhadap Tuhan Yang Maha Esa Studi Pada Kelompok Paguyuban Budaya Bangsa Di Jawa Tengah - Ceprudin, Ceprudin; Mustolehudin, Mustolehudin; Masfiah, Umi (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2024)
This research aims to reveal the survival strategies of the Faith Believers group (adherents of non-six religions in Indonesia) at the National Cultural Association (PBB). Presenting methods of resilience for the members of the Faith at this time is important as a guide to good practice (best practice) for fellow Believers. Examining group survival strategies Beliefs are closely linked to a history full of repression and discrimination. The National Cultural Association (PBB) is a group of believers who, according to organizational policy, choose not to join any religion. This type of research uses a juridical-empirical approach. This research was conducted in Kebumen Regency (central management) and Banjarnegara Regency (largest mass base) for PBB Faithful residents. Data sources were obtained from interviews with organizational leaders, young people and students who experienced pressure while being members of the PBB Faith. The author hypothesizes that PBB adherents are a group that firmly adheres to the teachings of their ancestors. Even though they face great pressure, they are still able to survive and carry out regeneration until now.